Papel do sistema histaminérgico na memória emocional de camundongos expostos e reexpostos ao labirinto em cruz elevado - Gianlorenço, Anna Carolyna Lepesteur (2010)
The aim of this study was to assess the influence of histaminergic substances on anxiety and emotional memory in mice exposed and re-exposed to the Elevated Plus-Maze (EPM). For this, two experiments were conducted. Experiment 1 evaluated the effects of L-histidine on anxiety and emotional memory and contribution of the H 1 antagonist (chlorpheniramine) for these effects. Experiment 2 evaluated the effect of chronic treatment with chlorpheniramine (CPA) on anxiety and emotional memory. The experiments were performed with Swiss-albino mice (25-35g), using the model of the EPM in two consecutive days, exposure (T1) and reexposure (T2). In experiment 1, animals received combined intraperitoneal injection pretrial in T1: SAL/SAL (saline + saline), LH/SAL (L-histidine 500mg/kg + saline) and LH/CPA (Lhistidine + Chlorpheniramine 16mg/kg). The combined injection was executed by one first injection, followed by a second injection 30 minutes later. The test was performed in the EPM 10 minutes after the last injection. Each animal was positioned on the center platform of the maze facing the open arm and had five minutes to explore. After 24 hours (T2), the animals received the same pharmacological treatment of the previous day and were re-exposed to the EPM, following the procedures described. In experiment 2, the procedure was the application of chronic injections of SAL or CPA, intraperitoneally (i.p.) for 15 days. After this period, on the first day of test (T1), the animals were injected i.p. with SAL or CPA and 40 minutes later were exposed to EPM for 5 minutes. In T2, the animals received the same pharmacological treatment the previous day and were re-exposed to the EPM. For each dose of CPA (8mg/kg and 16mg/kg) the animals were separated into four groups based on chronic treatment. In both experiments, the tests were recorded for the analysis of ethological measures and conventional measures [number of entries in open arms (OAE), enclosed (EAE) and total number of entries (TE), time spent in open arms (OAT), enclosed (EAT) and central area (CT), and their respective percentages]. Anxiety was assessed by the activity in the open arms (OA) in T1 (OAE, %OAE, OAT and %OAT), and decreased exploration of open arms on re-exposure was considered indicative of learning and memory. For data analysis, ANOVA (Two-way) followed by multiple comparison test Student-Newman-Keuls (SNK) (p <0.05) were used. The results of experiment 1 did not show difference between the groups in the variables related to exploration in the open arms (OAE, %OAE, OAT and %OAT). The control group SAL/SAL and the LH/CPA group had a significant reduction in these variables in T2, which was not observed in the group treated with LH/SAL. There was no significant change in locomotor activity in either group. The results of experiment 2 showed no significant difference between groups in variables related to anxiety, and there was no significant change in locomotor activity. Only the group treated exclusively with CPA (16mg/kg) showed significant reduction in measures OAE, %OAE, OAT and %OAT between test days (SNK <0.05). The results of experiment 1 indicated that the L-histidine caused a deficit in acquisition or recall of information of aversive open arms, and that chlorpheniramine was able to reverse this effect, suggesting the action of LH via the H1 receptor. The results of experiment 2 indicated that the chronic application of CPA did not affect the anxiety levels of mice exposed to the EPM and the information of aversive OA obtained in T1 was recalled only for animals treated exclusively with CPA (16mg/kg).